The synonymy of the genus Permixtimella Guţu, 2016 (Crustacea: Tanaidacea) with Ektraleptochelia Bamber & Marshall, 2015 and remarks on other leptocheliid taxa - Guțu, Modest; Bird, Graham J. (Zootaxa, 2017)
Guţu (2016) described a new subfamily, seven new genera and 21 new species in the family Leptocheliidae. However, another five genera and twelve new species, not mentioned by him, were described in 2015 and 2016. Study of the overlooked genera reveals that the morphology of the female of Permixtimella (genus described from both sexes) is similar to those of the type-female of the genus Ektraleptochelia (whose male is unknown). Permixtimella is considered a junior synonym of Ektraleptochelia, which includes two species: E. phoxops and E. oculifurcillata. The place of Ektraleptochelia, Catenarius and Larsmentia within leptocheliid systematics, formerly in the subfamily Catenariinae, is reconsidered and the last genus retained. Some similarities between the females of Nuberis and Bathyleptochelia are presented for the first time. The species Leptochelia acrolophus, L. mexicana, L. ortizi, L. taitungensis and L. grandidentata are transferred to other genera, becoming Chondrochelia acrolophus, C. mexicana, C. ortizi, C. taitungensis and Makassaritanais grandidentatus, respectively. The species Leptochelia pinarensis and L. suhi are considered a junior synonym of Leptochelia forresti and Makassaritanais grandidentatus, respectively.